Lovebugs in Florida - J. Weston; D.E. Short; M. Pfiester (EDIS, 2011)
This document provides an overview of lovebugs in Florida, detailing their identification, life cycle, mating behavior, and impact on motorists. Lovebugs, native to the United States, are known for their nuisance to drivers due to their swarming near highways. Despite their drawbacks, they play a beneficial role in decomposing vegetation and pollination. The article also discusses methods to mitigate their impact on vehicles and highlights natural predators that help control their population. Date first printed: October 1993.